Thyroglobulin Antibodies as a Prognostic Factor in Papillary Thyroid Carcinoma Patients with Indeterminate Response After Initial Therapy - Landenberger, Giullia Menuci Chianca; de Souza Salerno, Marianna Lins; Golbert, Lenara; de Souza Meyer, Erika Laurini (Hormone and Metabolic Research, 2020)
The clinical outcome of papillary thyroid carcinoma (PTC) patients with an indeterminate response after initial therapy is reported to be intermediate, between incomplete and excellent responses. This study evaluated the outcomes of PTC patients with indeterminate response after initial therapy. It was further determined whether the indeterminate findings predicted outcomes more precisely. Patients were further classified into 3 groups based on risk of structural persistence/recurrence: Tg group: detectable thyroglobulin, negative antithyroglobulin antibody, regardless nonspecific imaging findings; TgAb group: positive antithyroglobulin antibody, regardless thyroglobulin levels and nonspecific imaging findings, and Image group: nonspecific findings on neck ultrasonography or faint uptake in the thyroid bed on whole-body scan, undetectable thyroglobulin and negative antithyroglobulin antibody. Sixty-six patients aged 44.1±12.7 years were studied, of whom 58 (87.9%) were females. All patients underwent total thyroidectomy, and 52 patients (78.8%) received radioiodine. After 5.7 years (P25–75 2.6–9.75 years) of follow-up, most patients (89.4%) were reclassified as having an excellent response or remained in the indeterminate response to therapy. Structural recurrence/persistence disease was detected in 7 (10.6%) patients. The persistence/recurrence rate in groups were as follow: Tg, 2.63%; TgAb, 31.25%; Image, 8.3% (p=0.007). The 10-years disease-free survival rate in the TgAb group was significantly reduced (p=0.022). Our results suggest that patients with PTC and indeterminate response due to positive serum antithyroglobulin antibody have more risk of development of structural disease. These findings suggest a more individualized follow-up strategy for patients with an indeterminate response.
Keywords: dynamic risk stratification; initial response to therapy; recurrence